The Use of Demonstration to Improve the Mastery of Basic Movements in Soccer of Students at Fourth Grade of Public Elementary School 2 of Kalianget in the First Semester of 2018/2019 Academic Year - Prawoto . (Pancaran Pendidikan, 2019)
The demonstration method is a way of presenting lessons by demonstrating a process. This can be done both in actual form and in imitation form. Through demonstration, learning outcomes are achieved by students by involving all their potential after conducting learning activities. Achievement of learning outcomes can be measured by assessment of learning outcomes tests. The purpose of this study was to determine the increase in students’ mastery of basic soccer movement and to determine the effect of learning motivation on soccer basic movement of fourth-grade students at Public Elementary School 2 of Kalianget in Banyuglugur district, Situbondo regency after using the demonstration method. This research uses action research in two cycles. Each cycle consists of four stages: design, activity and observation, reflection, and revision. The subjects of this study were The fourth grade Public Elementary School 2 of Kalianget, Banyuglugur district, Situbondo regency. Analysis results show that student learning outcomes have increased. The students achieved 70.83% with an average value of 71.87 in the first cycle, while in the second cycle 87.5% completeness with an average value of 77.5 was evident. The conclusion of this research is the demonstration method can improve the learning outcomes of mastery of basic soccer movement of students at The fourth grade Public Elementary School 2 of Kalianget  Banyuglugur district Situbondo regency Semester I in 2018/2019 Academic Year.